Engineering polymerases for new functions - Coulther, Timothy A. (Trends Biotechnol, 2019)
DNA polymerases are critical tools in biotechnology, enabling efficient and accurate amplification of DNA templates, yet many desired functions are not readily available in natural DNA polymerases. New or improved functions can be engineered in DNA polymerases by mutagenesis or through the creation of protein chimeras. Engineering often necessitates the development of new techniques, such as selections in water-in-oil emulsions that connect genotype to phenotype and allow more flexibility in engineering than phage display. Engineering efforts have led to DNA polymerases that can withstand extreme conditions or the presence of inhibitors, as well as polymerases with the ability to copy modified DNA templates. This review discusses polymerases for biotechnology that have been reported, along with tools to enable further development.